Maternal fertility and child health in Ethiopia - TEFERI, Mulugeta Berie (KDI School, 2019)
To determine the casual link between fertility and its impact on child health this paper used an Instrumental variable (IV) estimation method. The Ethiopian Demographic and Health Survey of 2011 and 2016 is used to estimate impact of fertility on child health. Child health as dependent variable is measured by height-for-age Z score for stunting, while fertility stands for the number of children a woman gave birth to. Because of the joint determination nature of child health and fertility Simultaneous Equation Model (SME) with an IV estimation method is used, to deal with the endogeneity problem which arises from simultaneity, twin birth and same sex of the first two children of a woman is used as IV for fertility. The result indicates that there is a significant and strong causation between child health and fertility in Ethiopia. One additional birth of a woman will negatively affect the health of a child by 0.511 standard deviation. In addition to fertility regional places of residence are has strong and significant impact on child health in Ethiopia, while mother specific endowments in birth has lesser impact.
Thesis(Master) --KDI School:Master of Development Policy,2019